2011
DOI: 10.1128/jcm.00472-11
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas aquariorum Is Widely Distributed in Clinical and Environmental Specimens and Can Be Misidentified as Aeromonas hydrophila

Abstract: Genotypic characterization of 215 Aeromonas strains (143 clinical, 52 environmental, and 20 reference strains) showed that Aeromonas aquariorum (60 strains, 30.4%) was the most frequently isolated species in clinical and water samples and could be misidentified as Aeromonas hydrophila by phenotypic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
55
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 17 publications
3
55
1
1
Order By: Relevance
“…The authors reported that correct identification had occurred in only about one-third of 104 strains that had been identified as A. hydrophila based on phenotypic characteristics. In contrast, two-thirds of the isolates were re-identified as non-hydrophila Aeromonas, with most being A. aquariorum strains (54 strains, 51.9 %) [2]. The same result was obtained in another case study by Wu et al [3], who described a cirrhotic patient who developed septicemia caused by A. aquariorum, which was initially identified as A. hydrophila based on the results of biochemical tests.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…The authors reported that correct identification had occurred in only about one-third of 104 strains that had been identified as A. hydrophila based on phenotypic characteristics. In contrast, two-thirds of the isolates were re-identified as non-hydrophila Aeromonas, with most being A. aquariorum strains (54 strains, 51.9 %) [2]. The same result was obtained in another case study by Wu et al [3], who described a cirrhotic patient who developed septicemia caused by A. aquariorum, which was initially identified as A. hydrophila based on the results of biochemical tests.…”
supporting
confidence: 51%
“…However, such biochemical tests are unreliable to accurately identify Aeromonas to the species level. For example, Aravena-Román et al recently investigated 215 Aeromonas strains, including A. hydrophila, which represented more than 50 % of strains [2]. All of the isolates, which had been previously identified by a conventional biochemical scheme, were subjected to analysis of their nucleotide sequences derived from the gyrB and rpoD genes.…”
mentioning
confidence: 99%
“…This bacterium was also occasionally isolated from stranded elephant seals, California sea lions and harbour seals (Thornton et al 1998). It is possible that the A. hydrophila identified phenotypically in those studies could belong, after a genetic identification, to A. dhakensis (synonym of A. aquariorum), as occurred in previous studies (Figueras et al 2009, Aravena-Román et al 2011, Morinaga et al 2013). In our case, pathologic and bac teriologic examination revealed an acute haemorrhagic-necrotizing pneumonia and sepsis associated with A. dhakensis, which was recovered in pure culture from lung, liver, spleen, kidney and blood.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, it is the first time this species has been isolated in Sri Lanka. Isolation of this seemingly globally distributed species (Aravena-Román et al 2011, Yi et al 2013) from diseased ornamental fish provides additional evidence that a diverse range of motile aeromonads could potentially be associated with septicaemia in ornamental fish. The occurrence and pathogenesis of these rarely isolated motile aeromonads in tropical aquarium fish are not well understood and deserve further study.…”
Section: Discussionmentioning
confidence: 99%